Thrust Roller Control in Kiln using PLC and HMI - KUSUMA, ARI; Sardi, Juli; Habibullah; Ricky Maulana (Journal of Industrial Automation and Electrical Engineering, 2025)
The thrust roller control and monitoring system is very important in the cement production process, especially in the cement processing process that occurs in the Kiln equipment. At PT. Semen Padang, the thrust roller control and monitoring process using a potentiometer sensor often experiences problems. Based on this, this study aims to develop a solution to the problem of the thrust roller control and monitoring system to make it more accurate. This study was conducted using an experimental method. With this method, the author took some test data on the ultrasonic sensor as a substitute for the potentiometer sensor and then compared the test data with the actual value to determine the level of feasibility and error in the system. The research instrument used in the test was a meter while the object of the study was the thrust roller prototype that had been made. Based on the test results, the thrust roller control and monitoring system has been successfully carried out where the thrust roller movement is displayed in the form of an HMI screen simulation with a small error rate, namely from 20 trials 18 of them were successful while the remaining two experienced errors